Communication And Digitality In Anti-Vaccine Community Behavior Reconstruction - Sari, Ani Herna; Sugihartati, Rahma; Wulan, Nur; Hakim, Lukman (Jurnal Komunikasi, 2022)
Communication is growing with the advancement of digitalization. This led to the emergence of behavioral construction in society in response to a phenomen. Various patterns of social communication are deliberately carried out to achieve certain interests, but in fact, social communication does not always run in a positive direction and benefit many parties. In the anti-vaccine community in some areas of Surabaya shows that social communication carried out in a negative direction is in the act of mass vaccine rejection. This is certainly interesting, because social communication that is done with manners, manners, and background emotions and solidarity actually leads to the act of constructing behavior. This study will examine digitalization and communication on the construction of anti-vaccine community behavior in the city of Surabaya. The approach taken is qualitative, while the ethnographic method is chosen to obtain relevant data on a daily phenomenon. The results of this study found that digital media in conducting intensive social communication was able to foster behavioral reconstruction. Sharing behavior that was initially believed to be true was deliberately spread, but with the existence of information in digital media, it is able to destroy the power of subjective reality that is created. Communication in digital media is certainly not the only factor, but with the intensification of social communication, social reconstruction can occur again and again.